Reconciling the Irreconcilable: A Property Rights Approach to Resolving the Animal Rights Debate - Cesario Anthony J. (Studia Humana, 2021)
Libertarianism is understood to be a “deontological theory of law” that purportedly applies exclusively to humans. According to some libertarians, however, “one of the greatest weaknesses of libertarian theory” is that there are no provisions outlawing the abuse and torture of animals even though this seems to be one of “the most heinous acts it is possible to do”. Moreover, a few of these libertarians go even further and claim that this legal philosophy of non-aggression should actually be extended to include other animals. The purpose of this paper is to reconcile this seemingly irreconcilable situation by arguing that it is a “continuum problem” and offering a principled, libertarian compromise that resolves the animal rights debate using the non-aggression principle (NAP) and private property rights.